Valor nutricional del maguey deshidratado de cacao (Theobroma cacao L.) nacional para la elaboración de barras nutricionales de uso alimentario. - Morejon Lucio, Rocío Natividad (2016)
The aim was determine the nutritional value of dried maguey cocoa (Theobroma cacao L.) National to elaborate nutritional bars. Was utilized a Design Completely Random applied within a bifactorial array using three methods of dehydration with three methods, and three repetitions. The Tukey test (p≤0.05) for the physicochemical variables was evaluated, T1, T4, T6 and T5 (forced air oven, to bake and osmotic dehydration with honey was used to determine differences between means of physico-chemical analysis and baking with glucose syrup) they are the best treatments. The higher protein content (8.25%) and fiber (8.63%) presented the treatments T8 and T2 (forced air heater and osmotic dehydration glucose syrup). Sensory analysis of Kruskal Wallis test was applied to the respective Ward dendrogram using Euclidean distance, the best treatment was the T5. Microbiological analysis it was concluded that all treatments evaluated met the Standard NTE INEN 2085: 2005 for cookies or baked goods. As for the cost/benefit ratio recording the highest value the treatment T3 (forced air heater and molasses) with $ 0.39 for every dollar invested, with a gain of 39.14%.